Telaah Kegiatan Pijat Bayi Di Cilacap Perkotaan - Tri Budiarti; Frisca Dewi Yunadi (HB PRESS, 2018)
Growth and development moment a baby is a most critical, golden, and time of opportunity that can be stimulated by massage. In Cilacap, baby massage is often be done and not only done by traditional masseurs but also salons and clinics. The study aimed to find out information on baby massage in Cilacap. The study was qualitative with the RAP approach, the locations are Cilacap Utara, Cilacap Selatan, and Cilacap Tengah, informans consist of 20 parents, 8 massagers and 8 representatives of clinic or health center leaders and 1 representative of the Health Office using interview guidelines and analyzed and concluded. The results in the form of knowledge of informants mostly unknowing the meaning, benefits, or condition of a baby who is massaged. The motivation of most informants are to follow parents or family traditions. The attitude of the informants was mostly positive but the massage was a traditional masseurs. The baby's massage habits are mostly for health care